BIBLIOMETRIC ANALYSIS OF SAFETY MANAGEMENT: A COMPREHENSIVE REVIEW - Yudha, Dwi (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This article provides a comprehensive review of safety management research conducted between 1982 and 2023 using bibliometric analysis. The analysis of 969 articles published during this period shows that safety management research has steadily grown over the years, with the majority of research conducted in the United States and Europe. The most commonly mentioned term is